PEMBERDAYAAN SISWA SD II SESETAN DALAM MENGURANGI KASUS PENYAKIT DEMAM BERDARAH DI KELURAHAN SESETAN DENPASAR 2012 - D. S. Lubis; N. K Eka Wati; S. G. Purnama; K. Tresna Adhi; P. Suariani (Buletin Udayana Mengabdi, 2013)
This community service was conducted in SD N II Sesetan, Denpasar on 13 August 2012. The participants ofthis activity were 60 students from SD N II grade V Denpasar. Health education about the life span of denguefever mosquito and the common environment of the mosquito was delivered to the students. After being studiedin the class, the activity was continued by identification of jentik at the field. The aims of this activity are tostrengthen the role of students in reducing dengue fever cases in Sesetan village. Result of the pre-test and posttest showed an increase in knowledge of the students about dengue fever to overcome this disease. Statisticalanalysis showed a significant differences (P<0.05) between pre-test and post test. Students were asked to identifypotential container of mosquite which may be bred at home. There were 221 containers examined by students,and 26% of the containers have larva. It can be concluded that this activity can improve knowledge about denguefever and larva identification skill. This activity might become a good example to initiate elementary school basedprogram to eradicate dengue fever cases in Sesetan Village. It is recommended to scale up this activity to otherschool in order to strengthen the role of students in dengue fever prevention approach in Sesetan Village.